Activation of the human beta-globin promoter in K562 cells by DNA sequences 5' to the fetal gamma- or embryonic zeta-globin genes. - Lin, H J (1987)
Regulatory sequences of the human fetal gamma-globin gene were studied by constructing composite gamma/beta globin promoters and comparing their function to that of intact beta promoters in human K562 cells. The beta-globin gene with either 1,600 or 127 basepairs of beta promoter sequence was not expressed after stable introduction into K562 cells, consistent with the known inactivity of the beta-globin gene in these cells. In contrast, a gamma/beta promoter composed of a gamma fragment spanning positions -408 to -137 joined to the 127-bp beta promoter was able to drive the beta-globin gene. The gene appeared to be inducible with hemin. A zeta-globin 5' flanking fragment also activated the beta promoter. The function of a series of composite gamma/beta promoters was then assessed by their ability to drive directly the neomycin resistance gene, again in stably transformed cells. The -408 to -137 gamma fragment activated the beta promoter in an orientation-specific manner in this assay. Deletion analysis showed that regulatory sequences were present between positions -259 and -137 of the fetal gamma-globin gene flanking region.